Variable uterine uptake of FDG in adenomyosis during concurrent chemoradiation therapy for cervical cancer - Yu, Jeong Il (The Korean Society for Radiation Oncology, 2011)
To avoid improper tumor volume contouring in radiation therapy (RT) and other invasive procedures, we report a case of uterine adenomyosis showing increased (18)F-fluorodeoxyglucose (FDG) uptake on positron emission tomography (PET)/computed tomography (CT) mimicking malignant tumor in a 44-year-old woman during concurrent chemoradiation therapy (CCRT) for uterine cervical cancer. The adenomyosis was not associated with her menstrual cycle or with normal endometrium uptake, and it resolved one month after completion of RT. This case indicates that uterine adenomyosis in a premenopausal woman may show false positive uptake of (18)FDG-PET/CT associated with CCRT.